Metabolic adaptation of pigs to a Mycoplasma hyopneumoniae and Lawsonia intracellularis dual challenge - Helm, Emma T (J Anim Sci, 2018)
Respiratory and enteric pathogens such as Mycoplasma hyopneumoniae (Mh) and Lawsonia intracellularis (LI) reduce lean accretion and feed efficiency (FE) in growing pigs. However, the metabolic mechanism by which this occurs is still unknown. Therefore, the primary aim of this study was to examine the metabolic adaptation of pigs presented with a dual Mh and LI challenge (MhLI). A secondary objective was to examine if selection for high FE, modeled by selection for low residual feed intake (RFI), alters molecular response to disease. Using a 2 × 2 factorial design, 6 littermate pairs from a high RFI (HRFI) and 6 littermate pairs from a low RFI (LRFI) line (barrows, 66 ± 2 kg BW) were selected, with 1 pig from each pair assigned to individual pens in either the challenge or the nonchallenge (control) rooms (n = 6 barrows per line/challenge). On days post inoculation (dpi) 0, MhLI pigs were inoculated intragastrically with LI and intratracheally with Mh. Pig and feeder weights were recorded at dpi 0, 7, 14, and 21. On dpi 21, pigs were euthanized and tissues and blood were collected. Markers of oxidative stress, skeletal muscle metabolism and proteolysis, and liver gluconeogenesis were evaluated to determine the effects of MhLI, RFI line, and their interaction. The interaction of line and challenge was not significant (P > 0.05) for any measure. Overall, MhLI pigs had lower ADG (38%, P < 0.001), ADFI (25%, P < 0.001), and G:F (19%, P = 0.012) compared with controls. As expected, LRFI pigs had lower ADFI (P = 0.028) for the same ADG, giving them greater G:F (P = 0.021) than HRFI pigs. Challenged pigs had greater reactive oxygen species (ROS) production in the LM and liver (P < 0.10) but did not have greater skeletal muscle proteolysis. Liver gluconeogenesis was also not upregulated (P > 0.05) due to MhLI. These results provide further evidence that selection for LRFI does not negatively affect response to disease. In addition, these results suggest that postabsorptive metabolic functions are altered due to MhLI challenge. The MhLI challenge induced mitochondrial dysfunction, evident by greater ROS production, and caused pigs to favor glycolytic energy generation. However, skeletal muscle proteolysis and liver gluconeogenesis were not upregulated during MhLI challenge. These data suggest that during mild disease stress, pigs can meet energy demands without reliance on nutrient mobilization and gluconeogenesis.